A Press Release as a Source of Learning about the Law - Patryk KUPIS (Communications of International Proceedings, 2021)
Jurisprudence distinguishes between the terms sources of law and sources of learning about the law. While sources of law are usually strictly specified by the legislator, the catalogue of sources of learning about the law is not categorically defined. In this paper the author compares these two terms and points to differences between them. He then presents the functions of sources of learning about the law and the proposed catalogue of these sources. A particular analysis will concern a broad understanding of a press release as a form of a source of learning about the law, that is as any release made public through mass media. The constant development of mass media, both in terms of their availability and the technological offer, allows for a conclusion that receiving information about the law by means of this channel will still grow in popularity. The author discusses the possible consequences of using a press release as a source of learning about the law, both by the sender and the recipient, and he also points to the related dangers.
Keywords: Law; Society; Electronic Communication; Mass Media